2014
DOI: 10.1371/journal.pone.0098861
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled 7 Expression Is Positively Regulated by SIRT1 and β-Catenin in Breast Cancer Cells

Abstract: The Wnt signaling pathway is often chronically activated in diverse human tumors, and the Frizzled (FZD) family of receptors for Wnt ligands, are central to propagating oncogenic signals in a β-catenin-dependent and independent manner. SIRT1 is a class III histone deacetylase (HDAC) that deacetylates histone and non-histone proteins to regulate gene transcription and protein function. We previously demonstrated that SIRT1 loss of function led to a significant decrease in the levels of Dishevelled (Dvl) protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 37 publications
(44 reference statements)
2
39
0
Order By: Relevance
“…Additionally, Tp63 was shown to regulate expression of FZD7 and to enhance Wnt signaling in mammary normal and malignant tissue (48). A putative crosstalk between Wnt/b catenin pathway and ΔNp63, the TP63 isoform lacking the N-terminus domain, was reported in skin, hair follicles, mammary glands and limb buds during development (50). We observed a similar direct and strong correlation between TP63 and FZD7 expression levels in OC cells, supporting that expression of this receptor may be regulated by this transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Tp63 was shown to regulate expression of FZD7 and to enhance Wnt signaling in mammary normal and malignant tissue (48). A putative crosstalk between Wnt/b catenin pathway and ΔNp63, the TP63 isoform lacking the N-terminus domain, was reported in skin, hair follicles, mammary glands and limb buds during development (50). We observed a similar direct and strong correlation between TP63 and FZD7 expression levels in OC cells, supporting that expression of this receptor may be regulated by this transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, DVL-1 was shown to bind to a 2kb region upstream of the transcription start site of the Frizzled 7 gene in T-47D breast cancer cells. Interestingly, this binding was shown to be diminished with SIRT1/2 pharmacological inhibition, suggesting that DVL-1 protein levels and promoter occupancy could be regulated by at least one type of lysine deacetylase [19]. In addition, DVL was shown to modulate Wnt signaling by interacting with nuclear proteins such as HIPK1(Homeodomain-interacting protein kinase 1), xNET1 (Xenpous nucleotide exchange factor), and FOXKs (Forkhead box transcription factor) [2022].…”
Section: Function Of Dvl In Wnt Signaling Pathwaymentioning
confidence: 99%
“…Frizzled7 (FZD7) is a critical receptor for the WNT/β-catenin signaling pathway (16,17). Various studies have reported that FZD7 plays an important role in many types of human cancers, including renal cell carcinoma (18), cervical cancer (19), ovarian cancer (17), breast cancer (20), colon cancer (21), and hepatocellular carcinoma (22). It participates in carcinogenesis mainly through promoting the activation of the WNT/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%